Strategies for application of tucumã oil (Astrocaryum vulgare Mart.) in food products and food packaging: microencapsulation and oleogelation - Santos, Priscila Dayane de Freitas (2023)
The first objective of this work was to microencapsulate tucumã oil by spray drying (SD), spray chilling (SC) and the combination of these processes (SDC) and to characterize the microparticles regarding their physicochemical properties, microstructure, carotenoid and oxidative stability, the carotenoid release and β-carotene bioaccessibility of encapsulated oil after simulated digestion; the second aim was to evaluate the effects of incorporating encapsulated and non-encapsulated tucumã oil on extruded sheets; and the third objective was to apply the direct oleogelation at high temperatures and an indirect approach based on oil in ethanol/water emulsification at low temperature to structure tucumã oil with ethyl cellulose (EC), comparing the oleogels in terms of the retention of sensitive bioactives, rheological and physical aspects. The oil presented high contents of total carotenoids, β-carotene, and α-tocopherol. All the techniques applied to produce microparticles resulted in fine yellow powders and provided high carotenoid and oxidative stability to the encapsulated oil during long-term storage. Microencapsulation by SD resulted in water dispersible powders with increased oxidative stability at high temperatures and gradual release of carotenoids during in vitro digestion. But only SC microparticles could improve the bioaccessibility of β-carotene after simulated digestion. The incorporation of non-encapsulated and encapsulated tucumã oil into cassava starch formulations subjected to extrusion resulted in slightly yellow sheets with increased opacity and reduced solubility in water, indicating higher light barrier and lower biodegradability, respectively, while the mechanical strength of the sheets was significantly and negatively affected only by the SDC microparticles. Regarding tucumã oil oleogels, the use of high temperatures during direct oleogelation promoted the partial degradation of carotenoids and tocopherols of the oil and provided gels with weak structures. On the other hand, the indirect oleogelation resulted in harder oleogels with a more organized EC network, besides preventing bioactive losses due to the mild temperatures applied in this process. The present work contributed to expanding the knowledge on the application of different technologies to tucumã oil to produce new food ingredients and additives with high contents of bioactive compounds and varying functionalities. The promising properties of tucumã oil microparticles and oleogels make them suitable to enrich a range of food products, cosmetics, and packaging materials.